2020
DOI: 10.1111/cas.14438
|View full text |Cite
|
Sign up to set email alerts
|

Plastin 1 drives metastasis of colorectal cancer through the IQGAP1/Rac1/ERK pathway

Abstract: Tumor metastasis is the dominant cause of death in colorectal cancer (CRC) patients, and it often involves dysregulation of various cytoskeletal proteins. Plastin 1 (PLS1) is an actin‐bundling protein that has been implicated in the structure of intestinal epithelial microvilli; however, its role in CRC metastasis has not yet been determined. In this study, we demonstrated that PLS1 is highly expressed in 33.3% (45/135) of CRC patients and is correlated with lymph node metastasis and poor survival. In in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…We have further found that diallyl disulfide (DADS) inhibits the migration and invasion of colorectal cancer cell line SW480 by regulating the Rac1-ROCK1/PAK1-LIMK1-ADF/cofilin signaling pathway (104,105). Zhang, et al found that Plastin1 (PLS1), which is related to the microvilli structure of the intestinal epithelium, drives the metastasis of colorectal cancer through the IQGAP1-Rac1-ERK pathway (106). Overexpression of phospholipid phosphataserelated protein 1 (PLPPR1) in the mouse neuroblastoma cell line (Neuro2a) reduces the level of active Rac1.…”
Section: Rac1 Participates In Tumor Migration and Invasionmentioning
confidence: 94%
“…We have further found that diallyl disulfide (DADS) inhibits the migration and invasion of colorectal cancer cell line SW480 by regulating the Rac1-ROCK1/PAK1-LIMK1-ADF/cofilin signaling pathway (104,105). Zhang, et al found that Plastin1 (PLS1), which is related to the microvilli structure of the intestinal epithelium, drives the metastasis of colorectal cancer through the IQGAP1-Rac1-ERK pathway (106). Overexpression of phospholipid phosphataserelated protein 1 (PLPPR1) in the mouse neuroblastoma cell line (Neuro2a) reduces the level of active Rac1.…”
Section: Rac1 Participates In Tumor Migration and Invasionmentioning
confidence: 94%
“…PLS1 (plastin 1) is one of the actin-binding protein family members that are conserved throughout eukaryote evolution. PLS1 drives metastasis of colorectal cancer through the IQGAP1/Rac1/ERK pathway ( Zhang et al, 2020 ) and promotes osteoblast differentiation by regulating intracellular Ca2+ ( Wang L. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of in vivo experiments, it was shown that thiopurines treatments (TG) inhibited CAC in the AOM/DSS mouse model, via decreased β-catenin in a RAC1-dependent mechanism [ 144 ]. In the context of epithelial cell targeting, EMT and metastatic potential might be inhibited upon activation of RAC1; for instance, upon CSRP2 treatment (Hippo-ERK-PAK/LIMK/cortactin) [ 145 ], miR-142-3p transfection [ 146 ], upregulation of SSH3 (LIMK) [ 147 ] or PLS1 (ERK1/2) [ 148 ], downregulation of DMTN [ 149 ], or IRF1 suppression [ 150 ]. Recent work from An et al revealed the different behavior of RAC1 inhibition in combination with irradiation on cell cycle.…”
Section: Rac1 (Ras-related C3 Botulinum Toxin Substrate 1)mentioning
confidence: 99%